THE EFFICACY OF 'THE TORTOISE AND THE HARE' FOLKTALE IN ENHANCING NARRATIVE WRITING SKILLS OF JUNIOR HIGH SCHOOL STUDENTS: A QUALITATIVE STUDY - Zainuddin Hasibuan (JETAL: Journal of English Teaching & Applied Linguistic, 2026)
This research explains the efficacy of “The Tortoise and the Hare” folktale as a medium to enhance narrative writing skills in ELT (English Learning Teaching) in the junior high school. The findings show that the efficacy of folktales into writing instruction provides not only authentic language exposure but also fosters creativity, improves narrative structure, and increases students’ motivation. Some students demonstrated notable progress in organizing ideas, using richer vocabulary, and expressing themselves with greater confidence and coherence. The learning process is supported through visual aids, peer collaboration, scaffolding, and reflective tasks, which helped address common writing difficulties such as grammar challenges and fear of making mistakes. The story-based approach also facilitated deeper emotional and cognitive engagement by connecting language learning with moral values. As a result, writing became a tool for both linguistic improvement and self-expression. This study concludes that folktales are valuable pedagogical tools for enhancing writing instruction in ELT settings and recommends further exploration of culturally relevant stories and multimodal storytelling in future research.